An Educational Tool Aimed at Learning Metaheuristics - Kader, Md. Abdul; Jamaluddin, Jamal A.; Kamal Z., Zamli (Association for Computing Machinery, 2020)
In this paper, we introduce an education tool for learning metaheuristic algorithms that allows displaying the convergence speed of the corresponding metaheuristic upon setting/changing the dependable parameters. This tool can be an educational assistant for beginners to learn metaheuristic in theoretical lectures as well as practical sessions. Implemented with Java, this tool provides a friendly GUI for setting the parameters and display the result from where the learner can see how the selected algorithm converges for a particular problem solution. Initially, this tool adopts only Crow Search, Jaya, and Sine Cosine algorithms. But more metaheuristics will be included in future research. However, this application is a useful tool that will help not only beginner learners but also the researchers. This paper also describes the proposed software tool and the mentioned metaheuristics in detail and provides future research work on it.